Intervening in a “Sketchy Situation”: Exploring the Moral Motivations of College Bystanders of Sexual Assault - Gable, Samuel C. (Journal of interpersonal violence, 2021)
This mixed-methods research explored the moral motivations of undergraduates who identified as bystanders in a situation of potential sexual assault. In the quantitative analysis, we examined the difference between interveners and noninterveners with regard to their scores on the Moral Foundations Questionnaire–30 Item (MFQ-30), which considers five moral foundations from Moral Foundations Theory (MFT) of care/harm, fairness/cheating, loyalty/betrayal, authority/subversion, and sanctity/degradation, as well as measures of bystander attitudes (BAS-R) and rape-myth acceptance (IRMA, modified). Participants who failed to intervene had significantly higher scores on the loyalty/betrayal subscale of the MFQ-30, and showed a trend toward “conservative” values comprising the latter three MFT foundations. Intervening bystanders were also more likely to endorse bystander attitudes, and less likely to endorse rape-myth supporting beliefs. The qualitative analysis examined brief narratives in which participants described their bystander experience and reasoning in the moment. Analysis found a remarkable flexibility with which each moral foundation could be used to support either intervention or abstention. We argue that emphasizing conservative values (based on loyalty, purity, and/or authority) in addition to the typical liberal (justice-based and anti-harm) reasoning may bolster bystander interventions meant to reach all students.